Formulation of Lemongrass Extract Mouthwash (Cymbopogon Citratus) as a Non-Pharmacological Effort in Inhibiting The Growth of Bacteria That Cause Dental Caries - Purnama Fitri; Rasipin Rasipin; Ari Suwondo (Publikasi Indonesia, 2022)
Caries is a dental disease characterized by damage ranging from enamel, dentin, and pulp. Caries is caused by bacteria that stick to the teeth. The purpose of this study was to prove the effectiveness of lemongrass in inhibiting the growth of bacteria that cause dental caries. The pretest-posttest laboratory and field experiment consisted of a lemongrass mouthwash intervention group with concentrations of 33%, 36%, 39% and a chlorhexidine control group, each subject gargled for 2 minutes. Saliva was collected before and after gargling. The variables studied were the number of colonies and bacterial inhibition. The paired test of 36% (p=0.017) and 39% (p=0.006) concentration intervention groups was significantly different, while the chlorhexidine control group (p=0.091) was not significantly different. The organoleptic test results of the 36% lemongrass mouthwash had a dark brown color, slightly thick, the distinctive smell of lemongrass stems was still present, and the taste of mint. Based on this test, the most acceptable lemongrass mouthwash concentration is 36%. Giving a 39% lemongrass mouthwash formulation for 2 minutes effectively reduces the number of bacterial colonies that cause dental caries and the inhibition is better than the chlorhexidine control, while the 36% concentration is not significantly different from chlorhexidine.